2017
DOI: 10.1177/2325967117724416
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Factors in Tendon Injury: A Systematic Review of the Literature

Abstract: Background:Tendon injury such as tendinopathy or rupture is common and has multiple etiologies, including both intrinsic and extrinsic factors. The genetic influence on susceptibility to tendon injury is not well understood.Purpose:To analyze the published literature regarding genetic factors associated with tendon injury.Study Design:Systematic review; Level of evidence, 3.Methods:A systematic review of published literature was performed in concordance with the Preferred Reporting Items of Systematic Reviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 56 publications
0
21
0
1
Order By: Relevance
“…110 III Systematic reviews found that gene variants influenced the development of Achilles tendinopathy. 108,202 Specifically, genes associated with the collagen-production pathway may functionally affect tendon strength and stiffness, leading to an abnormal tendon response to loading. This was supported by other studies not included in this review.…”
Section: IImentioning
confidence: 99%
“…110 III Systematic reviews found that gene variants influenced the development of Achilles tendinopathy. 108,202 Specifically, genes associated with the collagen-production pathway may functionally affect tendon strength and stiffness, leading to an abnormal tendon response to loading. This was supported by other studies not included in this review.…”
Section: IImentioning
confidence: 99%
“…Nutrients penetrate through semipermeable membranes to promote the repair of injured cells and effectively enhance the endogenous healing of tendons. bFGF, HGF, and TGF- β 1 promote the differentiation, transformation, proliferation, and migration of stem cells and inhibit the growth of TGF- β receptors, which can prohibit the proliferation and differentiation of fibroblasts; downregulate the expression of α -smooth muscle actin, fibronectin, and integrin; reduce the biological function of fibroblasts and decrease fibrosis and scar formation [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Previous etiologic studies have indicated that environmental factors and self-diseases play important roles in the occurrence and development of chronic AT, such as age over 60 years, overuse, renal failure and diabetes mellitus 3 . Nevertheless, many case-control studies have found significant association signals between single nucleotide polymorphisms (SNPs) and chronic AT in Europeans 47 . Since chronic AT is a multifactorial disease with a complex genetic component, additional candidate genes should be investigated.…”
Section: Introductionmentioning
confidence: 99%